PER PADA SUB-SEKTOR BUILDING CONSTRUCTION - VINCENTIUS CLEMENT LALOAN; Satriyo Wibowo (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The aim of this research was to determine the effect of return on asset (ROA), debt to equity ratio (DER), dividend payout ratio (DPR), profit growth (EPS), and dividend yield (DY), on price earnings ratio (PER). The object research used building construction companies listed in the Indonesian Stock Exchange for 6 years with a research period from 2014 to 2020. The sample of this research using purposive sampling method and using 8 companies with a total data used of 56 company data. This study established five sample selection criteria and used the multiple regression analysis method. The results show that dividend payout ratio have a positive effect on price earnings ratio. While dividend yield has a negative effect on price earnings ratio and other variables in the form of return on asset, debt to equity ratio, profit growth have no effect on price earnings ratio.